La definicion del problema, el objetivo del programa de mejoramiento y planificacion del programa: aspectos claves y errores comunes - Beebe, Stephen E. (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
Important aspects involved in the establishment of a breeding program are indicated. The 1st step is to identify production constraints in order to define priorities. Solutions proposed should emphasize the improvement of materials or the adaptation and innovation of agronomic practices; this strategy requires genetic and environmental resources that allow the objectives of the breeding program to be assessed. (CIAT)